Digital Marketing Untuk Peningkatan Produktivitas Usaha Tape di Kabupaten Sumenep Madura - Rahem, Zaitur; Basid, Abdul (Yayasan Pondok Pesantren Sunan Bonang Tuban, 2024)
Tape entrepreneurs in Payudan Dundang and Pordapor villages have been pursuing this business conventionally since the beginning. The assistance aims to change methods from conventional to digital to become a solution in advancing the business of the Entrepreneurs in the two assisted villages. Assistance with digital marketing concepts is one of the effective methods of driving the economy of residents who focus on local potential. This tape productivity effort is not just an economic concept, but is also a way to solve the socio-economic problems of the interior which are getting worse with the existence of the modern market. Mentoring is carried out by opening initial communication with tape entrepreneurs at the mentoring location, seeing what business techniques are used, and planning the best mentoring method. The method used is advocacy, training and real action in utilizing natural materials around, and penetrating the modern market with tape packaging innovations.